Hydrological Responses of Agroforestry System Application which is Not Based on Land Suitability, A Case Study in Cimuntur Watershed - Edy Junaidi; Yonky Indrajaya (Foresty Faculty of Hasanuddin University, 2018)
Land use in a watershed should consider land capability and watershed carrying capacity so that the land can optimally. Agroforestry is a land use system that not only aims to generate income for the people but also to maintain hydrological conditions of a watershed. This research aims to evaluate the hydrological responses due to the application of agroforestry system on several land use pattern that has been changed. There are three steps in the analysis: (1) Assessment on land use planning (RTRW), (2) Land use suitability classification for agroforestry system, and (3) Development of scenarios for suitable land use of agroforestry system for hydrological function. The results of this study show that the application of agroforestry system of woody plant (i.e. sengon), fruit plant (i.e. Nephelium lappaceum), annual crops (i.e. clove, coconut, Parkia speciosa and banana), perennial crops (i.e. cardamom, and banana), and seasonal crops (i.e. cassava) on unsuitable land use gives the lowers on Coefficient of River Regime (KRS), specific discharge, Run off Coefficient (C) and Total Dissolve Sediment (TDS). This agroforestry system can be applied on several land use pattern that has been changed, because this system not only aims to generate income for the people but also to the maintain hydrological condition of a watershed